The Effectiveness of Using BBC Learning English on Teaching Students’ Speaking Skills: The Pre-Experimental Research on 8th Grade Students of SMPN 7 Sungai Raya in Academic Year 2024/2025 - Mubina, Muhammad Fathan; Yanti Sri Rezeki; Wardah (Jurnal Pendidikan Bahasa, 2025)
Abstract This study was carried out at SMPN 7 Sungai Raya, focusing on eighth-grade students, with the main goal of improving their speaking abilities. The research used a pre-experimental approach, which included a pre-test and post-test to measure the effectiveness of BBC Learning English in enhancing students' speaking skills. A total of 27 students from class 8D participated in the study. The pre-test involved an oral exam where students’ speaking skills were assessed before any intervention took place. After the pre-test, students received lessons that incorporated materials from the BBC Learning English platform. The post-test, which followed a similar format to the pre-test but with different questions, was given to evaluate the improvement in students’ speaking abilities after the treatment. The results revealed a significant improvement in the students’ speaking skills. The average score on the pre-test was 34, considered a poor score, while the post-test average rose to 72, categorized as good. This positive change was further supported by the statistical analysis, where the t-test value (12.3657) exceeded the t-table value (2.060), confirming that the difference between the pre-test and post-test scores was statistically significant. As a result, the alternative hypothesis (Ha), which suggested that BBC Learning English would improve students' speaking skills, was supported, and the null hypothesis (Ho) was rejected. In conclusion, the findings suggest that BBC Learning English is an effective tool for enhancing students’ speaking skills. The considerable increase in post-test scores highlights the positive impact of the platform. The study recommends incorporating BBC Learning English in language learning environments, as it offers interactive and engaging content that encourages students to practice and improve their speaking abilities. Furthermore, integrating such resources into the curriculum could help students gain more confidence and skill in using English for everyday communication.